Aldehyde dehydrogenase variation enhances effect of pesticides associated with Parkinson disease - Fitzmaurice, Arthur G; Rhodes, Shannon L; Cockburn, Myles; Ritz, Beate; Bronstein, Jeff M (Neurology, 2014)
The objective of this study was to determine whether environmental and genetic alterations of neuronal aldehyde dehydrogenase (ALDH) enzymes were associated with increased Parkinson disease (PD) risk in an epidemiologic study. A novel ex vivo assay was developed to identify pesticides that can inhibit neuronal ALDH activity. These were investigated for PD associations in a population-based case-control study, the Parkinson's Environment & Genes (PEG) Study. Common variants in the mitochondrial ALDH2 gene were genotyped to assess effect measure modification (statistical interaction) of the pesticide effects by genetic variation. All of the metal-coordinating dithiocarbamates tested (e.g., maneb, ziram), 2 imidazoles (benomyl, triflumizole), 2 dicarboxymides (captan, folpet), and 1 organochlorine (dieldrin) inhibited ALDH activity, potentially via metabolic byproducts (e.g., carbon disulfide, thiophosgene). Fifteen screened pesticides did not inhibit ALDH. Exposures to ALDH-inhibiting pesticides were associated with 2- to 6-fold increases in PD risk; genetic variation in ALDH2 exacerbated PD risk in subjects exposed to ALDH-inhibiting pesticides. ALDH inhibition appears to be an important mechanism through which environmental toxicants contribute to PD pathogenesis, especially in genetically vulnerable individuals, suggesting several potential interventions to reduce PD occurrence or slow or reverse its progression.